A study to assess the knowledge and attitude of female graduate students on cervical cancer - Koshy, George; Gangadharan, Vandana; Naidu, Anullekha (International Journal of Research in Medical Sciences, 2017)
Background: Cervical cancer is one of the most common cancers in women with an average of 468,000 new cases per year. Out of these 80% occur in developing and underdeveloped countries. World Health Organisation statistics show that Indian carries one fifths of world burden of the disease with 72,600 deaths annually. Key to the success of cervical cancer screening and prevention is the knowledge and awareness possessed by women in general. This requires the honing of knowledge at an impressionable and younger age group. Methods: It is a questionnaire based cross sectional study and was conducted amongst 4 study groups comprising Medical students, engineering students, nursing students and general graduate students between the age group 18 and 25 years. Results: According to present study, 93% of medical, 75% of nursing and only 29% of engineering students and 9 % of other students were actually even aware of the term cervical cancer. Assessment of knowledge regarding the risk factors of cervical cancer revealed that 13 medical, 9 nursing, 75 of engineering and 85 of Other Graduates weren’t aware of any risk factor that causes cervical cancer. As regards to attitude of the students towards cancer, present study revealed 4 medical, 23 nursing, 10 engineering and 9 general public women think that it is incurable and leads to death. Conclusions: This study highlights unawareness of various aspects of cervical cancer among young women and the burning need for continuing educational intervention at institute level to emphasise the importance and increase the awareness regarding cervical cancer.